Unusual records of marine organisms in the Neretva River (Croatia and Bosnia and Herzegovina) - Tutman, Pero; Dragičević, Branko; Dulčić, Jakov; Glamuzina, Luka; Bukvić-Metković, Višnja; Vekić, Josip (2021)
This paper presents a review of the unusual occurrences of various marine species found upstream in the Neretva River and its wider delta zone in the last two decades. The occurrences of at least eight different marine species were reported by local fishermen, representing very rare records of these species in the upstream areas of rivers. Although some of these species generally inhabit both saltwater and brackish waters, their occurrences high upstream are probably the consequence of changes in hydrological conditions in Neretva River. Namely, more intense saltwater intrusion into the river observed in the last two decades provides suitable conditions for mass penetration of euryhaline organisms high into the Neretva River. In this biodiversity rich area which hosts a significant number of endemic species, such phenomena can threaten the local freshwater communities.
U radu je prikazan pregled neobičnih nalaza morskih vrsta u rijeci Neretvi te širem području njene delte u posljednja dva desetljeća. Pojava najmanje 8 različitih morskih vrsta prijavljena je od strane lokalnih ribara, a radi se o općenito rijetkim nalazima morskih organizama u uzvodnim dijelovima riječnih tokova. Iako neke od vrsta opisanih u radu obitavaju i u slanim i u bočatim vodama, njihova pojava visoko uzvodno vjerojatno je posljedica promjena hidroloških uvjeta u rijeci Neretvi. Naime, intenzivniji prodor morske vode u rijeku u posljednja dva desetljeća omogućava masovno prodiranje eurihalnih organizama visoko u rijeku Neretvu. Na ovom području, bogatom biološkom raznolikošću sa značajnim brojem endemskih vrsta, takve pojave mogu ugroziti zajednice slatkovodnih organizama.
Bibliografija: str. 145-147.
Summary ; Sažetak.
Keywords: Morski organizmi; Neretva -- Hrvatska -- Bosna i Hercegovina